2016
DOI: 10.7150/thno.15088
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Biocompatibility, Biodistribution and Therapeutic Efficiency of Titania Coated Upconversion Nanoparticles for Photodynamic Therapy of Solid Oral Cancers

Abstract: Despite the advantages of using photodynamic therapy (PDT) for the treatment of head and neck tumors, it can only be used to treat early stage flat lesions due to the limited tissue penetration ability of the visible light. Here, we developed near-infrared (NIR) excitable upconversion nanoparticle (UCN) based PDT agent that can specifically target epithelial growth factor receptor (EGFR) overexpressing oral cancer cells, in a bid to widen the application of PDT against thick and solid advanced or recurrent hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…Efficacy studies reported that UCNs + NIR laser caused the highest tumor growth inhibition compared to NPs and PDT alone. In addition, treatment with UCNs + NIR laser resulted in larger areas of tumor necrosis and higher down-regulation of Ki67 than untreated controls [27].…”
Section: Other Types Of Magnetic Npsmentioning
confidence: 89%
See 4 more Smart Citations
“…Efficacy studies reported that UCNs + NIR laser caused the highest tumor growth inhibition compared to NPs and PDT alone. In addition, treatment with UCNs + NIR laser resulted in larger areas of tumor necrosis and higher down-regulation of Ki67 than untreated controls [27].…”
Section: Other Types Of Magnetic Npsmentioning
confidence: 89%
“…Due to their nano-size and the potential to modify their surface with antibodies, drugs, and MRI contrast agents, magnetic NPs have been used as theranostic agents [27][28][29]34]. In addition, they are capable of converting non-ionizing electromagnetic radiation produced by an energy source (e.g.…”
Section: Magnetic Npsmentioning
confidence: 99%
See 3 more Smart Citations